Mathematical Modeling and Modal Switching Control of a Novel Tiltrotor UAV - Zhiwei Kong; Qiang Lu (Journal of Robotics)
This paper concentrates on the flight control of a novel tiltrotor aircraft with fixed wings. This kind of aircraft has two flight modes and a transition mode. In the phase of vertical take off and landing (VTOL), the aircraft can operate as a quadrotor helicopter. And in the phase of horizontal flight, the aircraft is in the normal airplane mode. The transition mode is between these two flight modes. In this part of work, a novel tiltrotor aircraft was presented since transition mode is achieved by tilting the front dual tiltrotor (DTR) and the mathematical model was established. The classical PID method was used during the phase of VTOL and the numerical results were given and the simulation shows good control effect. A nonlinear control law based on backstepping was proposed to achieve a stable transition from vertical flight to horizontal flight. And the numerical results show that the flight mode could transit stably which shows the effectiveness of the control approach. Finally, the vertical flight experiment has been carried out on DTR aircraft and the attitude was stable.